Laju Pertumbuhan dan Produksi Jintan Hitam (Nigella sativa L.) dengan Aplikasi Pupuk Kandang Sapi dan Fosfat Alam - Ridwan, Taopik; Ghulamahdi, Munif; Kurniawati, Ani (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACT Black cumin (Nigella sativa L.) is a medicinal plant and spices belongs to the Ranunculaceae family. Black cumin seed contains some  secondary compounds and rich in nutrition that are beneficial  to health. The objective of this research was to investigate the effect of organic fertilizer rates on plant growth and production of black cumin (Nigella sativa L.). This research was conducted at Manoko Lembang, Bandung Barat from October 2012 to January 2013. The experiment was arranged in a randomized complete block design with three replications. The treatment consists of two factors, i.e. cow manure and rates of rock phosphate. Rates of cow manure applied were 0, 10, 20, and 30 ton ha-1, and rates of rock phosphate were 0, 40, 80, and 120 kg P2O5 ha-1. The results showed that cow manure increased plant height, leaf number, branch  number, flower  number, fresh weight and dry weight of branch, leaf and total plant weight. Rock phosphate fertilizer increased  leaf  area  and  leaf  area index of plant. Fertilizers that can efficiently increase production was 10 tons cow manure ha-1 and 40 kg P2O5 ha-1.Keywords: cow manure, growth, Nigella sativa L, production, rock phosphate